Celecoxib sensitizes imatinib-resistant K562 cells to imatinib by inhibiting MRP1–5, ABCA2 and ABCG2 transporters via Wnt and Ras signaling pathways. Issue 7 (July 2015) - Dharmapuri, Gangappa; Doneti, Ravinder; Philip, Gundala Harold; Kalle, Arunasree M.
Graphical abstract